Analisis Pendapatan Dan Resiko Usaha Budidaya Ikan Lele Dan Ikan Patin Di Kecamatan Way Panji Kabupaten Lampung Selatan - Meita Saniyyah Ubay; Anggun Safitri; Nanda Pardani (Prodi Agribisnis, 2025)
Lampung Province is a major producer of freshwater fish, particularly catfish and pangasius. Investigating the potential revenue and risks of catfish and pangasius farming in Way Panji District, South Lampung Regency, was the primary reason for this research. In this study, researchers surveyed forty-four pangasius farmers and forty catfish farmers. The coefficient of variance (CV) formula was used to calculate the risk. According to the study, catfish farming generated an average cash income of Rp11,146,179/100m² with an R/C value of 3.59, while patin fish farming generated an average cash income of Rp6,670,172/100m² with an R/C value of 1.64.